Biochemical and hematological alterations in mice inoculated with outer membrane protein, lipopolysaccharides and whole cells of Pasteurella multocida type B: 2 - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Osman, Abdinasir Yusuf; Haron, Abd Wahid; Saharee, Abdul Aziz; Abdullah, Rasedee; Saad, Mohd Zamri; Zakaria, Zunita (Science Publications, 2013)
Haemorrhagic septicaemia in cattle and buffaloes is an economically important livestock disease in Asia including Malaysia. Therefore, the aim of this study was to investigate the biochemical and hematological alterations in mice model inoculated with outer membrane protein, lipopolysaccharides and whole cells of Pasteurella multocida type B: 2. Two hundred healthy male mice of eight to ten weeks old were used in this study. The mice were divided into four equal groups of 50 mice each. Mice of group 1 were inoculated intra-peritoneal with 1.0 mL sterile Phosphate Buffered Saline (PBS) pH7, group 2 were inoculated with 1.0 mL of 109 colony forming unit (cfu) of P. multocida B: 2. Mice of groups 3 and 4 were inoculated intra-peritoneal with 1.0 mL of LPS and 1.0 mL of OMP, respectively. Blood samples were collected from the moribund animals and the biochemical and hematological parameters were assessed using ANOVA and Tukey-Kramer test. In the hematology, significant decreases were observed in the treatment groups compared to the control group. Increases were only observed in band neutrophils, eosinophils and plasma proteins in the treatment groups compared to the control group. In the serum biochemistry, significant increases were observed in the treatment groups compared to the control group. Decreases were only observed in AP and albumin: globulin ratio. In electrolytes, significant increases were observed in chloride and calcium in the treatment groups compared to the control. In conclusion, all the immunogen group of mice showed changes in complete blood count and biochemistry profiles with some differences between the groups.